ANALISIS KESULITAN MENULIS PUISI BEBAS - Windy Oktavia (Fakultas Ilmu Pendidikan Universitas Negeri Surabaya, 2019)
This study aims to describe whether the difficulty of writing poetry freely in fifth grade students of SD Negeri 4 Jelobo towards the five elements of poetry is how students understand the five elements of poetry. The research method used is to use qualitative research, where in the qualitative research the main instrument is the researcher himself. In this study the data collection techniques used included tests, interviews, questionnaires, and documentation. This research was conducted at SDN 4 Jelobo in January - February 2019. In this study, the validity of triangulation data was used. The results showed that the analysis of the difficulty of writing class V free poetry in the even semester of SD Negeri 4 Jelobo was quite well done, this activity was carried out by analyzing the elements of poetry including: diction, imagination, discussion, theme, and mandate in finding students' difficulties in writing poetry free.